Triacylglycerol biosynthesis: another cellular lipid pathway essential to HCV replication. (February 2011) - Andréé, Patrice; Enache, Liviu S; Ramièère, Christophe; Scholtes, Caroline; Lotteau, Vincent
Evaluation of: Herker E, Harris C, Hernandez C et al. : Efficient hepatitis C virus particle formation requires diacyglycerol acyltransferase-1. Nat. Med. 16, 1295––1298 (2010). Two diacylglycerol acyltransferase (DGAT) enzymes catalyze the final step of triglyceride synthesis, with structural, topological and physiological differences. They also contribute to the formation of cytosolic lipid droplets, which have been shown to play an essential role in HCV replication. Selective inhibition or silencing of DGAT1, but not of DGAT2, dramatically impaired the production and secretion of infectious virus, while leaving HCV RNA replication unaffected. An interaction between DGAT1 and core protein was demonstrated. The interaction between the two proteins appears to be independent of the catalytic activity of the enzyme, while its inhibition decreases the localization of core and HCV RNA onto the surface of lipid droplets. This study not only provides another piece of evidence of the pivotal role of lipids and lipid droplets in the viral life cycle, but also adds triglyceride synthesis to the cellular lipid pathways that are essential to the production of infectious viral particles.